THE EFFECT OF THE QUALITY OF SERVICE AND SATISFACTION OF THE UMRAH CONTRIBUTORS ON THE LOYALTY OF THE CONGREGATION IN PT MULTAZAM WISATA AGUNG MEDAN - Manuntun Pakpahan; Vini Alfionita (Universitas Negeri Medan, 2022)
PT. Multazam Wisata Agung Medan is one of the travel services in the city of Medan owned by Dr. Prof. H. Syafii Mukhoyyar Siregar, which is officially recognized by the Ministry of Religion. The problems in this study are whether the variable quality of service and satisfaction of umrah pilgrims together have a positive and significant effect on the loyalty of the congregation of PT. Multazam Wisata Agung Medan. The purpose of this study was to examine and find out whether there was an effect of service quality and satisfaction of umrah pilgrims on the loyalty of pilgrims at PT. Multazam Wisata Agung Medan. Data collection techniques were carried out by distributing questionnaires to respondents as many as 92 people from the congregation. The model used is multiple linear regression which is processed with the SPSS version 21 program. Service quality has a positive but statistically insignificant effect on Jamaah Loyalty at PT. Multazam Wisata Agung Medan. Statisfaction of umrah pilgrims has a positive and significant effect on the loyalty of pilgrims. And simultaneously there is a positive and significant influence between the variables of Service Quality and Satisfaction of Umrah Pilgrims of Jamaah Loyalty. The results of the coefficient of determination on the value of Adjusted R Square is 0,440 (44%). So that it can be said that 44% of the variation of the independent variable: Service Quality (X1) and Satisfaction of Umrah Jamaah (X2) in the model has contributed to the Loyalty variable of the PT. Multazam Wisata Agung Medan (Y) while the remaining 56% is influenced by other variables outside the model.